Gambaran Kesehatan Mental Emosional Melalui SDQ pada Siswa Kelas VI SDN Sambirobyong 1 - Sari, Melani Kartika; Susmiatin, Eko Arik (STIKES dan AKZI Karya Husada Kediri, 2024)
Children are the nation's next generation, therefore their health needs to be paid attention to, including mental health. Good mental health can help children manage their emotions well so they can live a good and healthy life. The aim of this research is to determine the mental health picture of class VI students at SDN Sambirobyong 1 through the Strength and Difficulties Questionnaire (SDQ). This research uses a descriptive analytical approach. The respondents of this research were 18 students at SDN Sambirobyong 1 who were in class VI. The questionnaire used is the Strength and Difficulties Questionnaire (SDQ). Assessment components include emotional symptoms, behavioral symptoms, hyperactivity symptoms, peer symptoms, and prosocial symptoms. The research results showed that 50% of students experienced emotional symptoms, 33% experienced behavioral symptoms, 5% experienced hyperactivity symptoms, 61% peer relationship problem symptoms, and 61% experienced prosocial symptoms. Students' mental health needs to be maintained, especially now that children's use of cellphones is also quite increasing and has the potential to cause emotional disorders in children if used excessively.